More than the barrier effect: Biodegradable Mg-Ag alloy membranes for guided bone/tissue regeneration - Sihui Ouyang; Xiong Wu; Li Meng; Xuerui Jing; Liying Qiao; Jia She; Kai Zheng; Xianhua Chen; Fusheng Pan (Journal of Magnesium and Alloys)
Magnesium (Mg) and its alloys have emerged as promising candidates for guided bone/tissue regeneration (GBR/GTR) due to their good mechanical properties, biosafety, and biodegradability. In this study, we present a pioneering application of Mg-Ag alloys featuring tunable corrosion behaviors for GBR/GTR membranes, showcasing their in vitro antibacterial effects, cell migration, and osteogenic differentiation abilities. Mg-Ag alloys with different Ag contents were engineered to facilitate the cell migration of murine fibroblasts (L929) and the osteogenic differentiation of rat bone mesenchymal stem cells (rBMSCs). The Mg-Ag alloy consisted of recrystallized α-Mg grains and fine Mg4Ag second phases, with an observable refinement in the average grain size to 5.6 µm with increasing Ag content. Among the alloys, Mg-9Ag exhibited optimal mechanical strength and moderate plasticity (tensile yield strength of 205.7 MPa, elongation of 20.3%, and a maximum bending load of 437.2 N). Furthermore, the alloying of Ag accelerated the cathodic reaction of pure Mg, leading to a slightly increased corrosion rate of the Mg-Ag alloys while maintaining acceptable general corrosion. Notably, compared with pure Mg, Mg-Ag alloys had superior antibacterial effects against Porphyromonas gingivalis (P. gingivalis) and Staphylococcus aureus (S. aureus). Taken together, these results provide evidence for the significant clinical potential of Mg-Ag alloys as GBR/GTR membranes.